2014
DOI: 10.1007/s11356-014-3683-0
|View full text |Cite
|
Sign up to set email alerts
|

Human health risk assessment of multiple contaminants due to consumption of animal-based foods available in the markets of Shanghai, China

Abstract: To assess the health risks due to food consumption, the human daily intake and uptake of organochlorine pesticides, polychlorinated biphenyls, polybrominated diphenyl ethers, polycyclic aromatic hydrocarbons, and toxic trace elements (mercury, chromium, cadmium, lead, and arsenic) were estimated based on the animal-based foods collected from markets in Shanghai, China. The estimated daily intake and uptake considering the contaminant bioaccessibility via single food consumption were 9.4-399 and 4.2-282 ng/kg b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(13 citation statements)
references
References 40 publications
1
12
0
Order By: Relevance
“…The total HRI (THRI) of heavy metals for sausage and ham was calculated according to Equation 3 (22,23): (3) T HRI = HRI (toxicant 1…”
Section: Analysis Of Food-related Health Risksmentioning
confidence: 99%
“…The total HRI (THRI) of heavy metals for sausage and ham was calculated according to Equation 3 (22,23): (3) T HRI = HRI (toxicant 1…”
Section: Analysis Of Food-related Health Risksmentioning
confidence: 99%
“…Concentrations of Cd and As in some samples of sparuslatus, N. coibor, R. philippinarum, and P. tenera were higher than the safety limits of national standards (Table 3). Here, we assumed that methyl mercury (MeHg) and inorganic As (InAs) constituted 62 % of the total Hg and 10 % of the total As, respectively (Liao and Ling 2003;Wang et al 2012;Ahmed et al 2015;Lei et al 2015).…”
Section: Heavy Metal Concentrationsmentioning
confidence: 99%
“…3a, b), which were calculated based on the CSF value of 1.5 (mg/kg/ day) −1 for InAs. However, a CSF value of 25.6 (mg/kg/day) −1 published in a recent toxicological review of InAs was suggested for calculation (EPA/635/R-10/001, 2010) and has been used in some researches (Yu et al 2014;Lei et al 2015). If this provisional CSF value was used in the calculation, the THQ values increased to 7.28-296 (Fig.…”
Section: Risk Assessment Of Dietary Heavy Metal Exposurementioning
confidence: 99%
See 2 more Smart Citations